Prólogo: The Europe that protects, from theory to practice through critical thinking and digital literacy - Fonseca Morillo, Francisco (Journal of Learning Styles, 2020)
Since the COVID-19 crisis dramatically affected the European Union (EU), we have seen the development and amplification of manifestly false narratives spread with the sole aim of damaging the action against the coronavirus and creating chaos or confusion. For example, from the EU we have identified and pointed out false narratives about the EU response or attitude towards the coronavirus, about COVID-19 and the refugees in the camps in Greece, about miracle cures.